Quantification techniques to minimize the effects of native T(1) variation and B(1) inhomogeneity in dynamic contrast-enhanced MRI of the breast at 3 T. - Azlan, C.A.; Ahearn, T.S.; Di Giovanni, P.; Semple, S.I.; Gilbert, F.J.; Redpath, T.W. (Wiley-Liss, 2011)
The variation of the native T(1) (T(10) ) of different tissues and B(1) transmission-field inhomogeneity at 3 T are major contributors of errors in the quantification of breast dynamic contrast-enhanced MRI. To address these issues, we have introduced new enhancement indices derived from saturation-recovery snapshot-FLASH (SRSF) images. The stability of the new indices, i.e., the SRSF enhancement factor (EF(SRSF) ) and its simplified version (EF'(SRSF) ) with respect to differences in T(10) and B(1) inhomogeneity was compared against a typical index used in breast dynamic contrast-enhanced MRI, i.e., the enhancement ratio (ER), by using computer simulations. Imaging experiments with Gd-DTPA-doped gel phantoms and a female volunteer were also performed. A lower error was observed in the new indices compared to enhancement ratio in the presence of typical T(10) variation and B(1) inhomogeneity. At changes of relaxation rate (ΔR(1) ) of 8 s(-1) , the differences between a T(10) of 1266 and 566 ms are <1, 12, and 58%, respectively, for EF(SRSF) , EF'(SRSF) , and ER, whereas differences of 20, 8, and 51%, respectively, result from a 50% B(1) field reduction at the same ΔR(1) . These quantification techniques may be a solution to minimize the effect of T(10) variation and B(1) inhomogeneity on dynamic contrast-enhanced MRI of the breast at 3 T. Magn Reson Med, 2011. © 2011 Wiley-Liss, Inc.